2018
DOI: 10.1021/acsnano.7b08539
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Graphene by Multiple Lasing: Toward Electronics on Cloth, Paper, and Food

Abstract: A simple and facile method for obtaining patterned graphene under ambient conditions on the surface of diverse materials ranging from renewable precursors such as food, cloth, paper, and cardboard to high-performance polymers like Kevlar or even on natural coal would be highly desirable. Here, we report a method of using multiple pulsed-laser scribing to convert a wide range of substrates into laser-induced graphene (LIG). With the increased versatility of the multiple lase process, highly conductive patterns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
829
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 731 publications
(895 citation statements)
references
References 22 publications
22
829
0
6
Order By: Relevance
“…Tour et al showed another example that commercial polyimide can be laser scribed into LSG by using a commercial CO 2 laser cutting machine ( Figure a) 225. Furthermore, they developed inert‐gas‐protected laser scribing and multiple laser scribing processes which enable the successful transformation from wood,226 cloth,227 bread into LSG (Figure 15b). Alshareef et al developed the LSG from natural lignin and used LSG as electrodes for high‐energy microsupercapacitors through a direct‐write lignin laser lithography technique 228.…”
Section: New Porogen Engineering Methodsmentioning
confidence: 99%
“…Tour et al showed another example that commercial polyimide can be laser scribed into LSG by using a commercial CO 2 laser cutting machine ( Figure a) 225. Furthermore, they developed inert‐gas‐protected laser scribing and multiple laser scribing processes which enable the successful transformation from wood,226 cloth,227 bread into LSG (Figure 15b). Alshareef et al developed the LSG from natural lignin and used LSG as electrodes for high‐energy microsupercapacitors through a direct‐write lignin laser lithography technique 228.…”
Section: New Porogen Engineering Methodsmentioning
confidence: 99%
“…[12] The I D /I G values of 0.79 and 0.64 are calculated from NiO/Co 3 O 4 /LIG and NiO/Co 3 O 4 -LIG-WPU, respectively, www.advmattechnol.de suggesting a relatively higher crystallized graphene without substantial structural defects was formed during the cocarbonization of gelatin-mediated ink and PI. [14] It is worth noting that the low-intensity peaks at low wavenumbers shows the evidence that the hybrid NiO/Co 3 O 4 nanoparticles existence, and the overall spectra is depicted in Figure S7 (Supporting Information). Whereas these characteristic peaks are not apparent after the transferring process since the mixed metal oxides were wrapped by the WPU thin layer.…”
Section: Morphology and Structure Analysismentioning
confidence: 94%
“…[10,11] Laser direct writing, a noncontact, fast, and one-step fabrication technique does not need masks, postprocessing, or complicated external environments and is considered as an ideal candidate for fabricating MSCs. [14,15] The as-prepared LIG electrodes, with a large accessible area, could be subsequently assembled into MSCs. [14,15] The as-prepared LIG electrodes, with a large accessible area, could be subsequently assembled into MSCs.…”
mentioning
confidence: 99%
“…[42] Graphene prepared using this technique can be integrated into energy storage devices such as supercapacitors (Figure 4). [42] Graphene prepared using this technique can be integrated into energy storage devices such as supercapacitors (Figure 4).…”
Section: Non-conventional Processing Of Ingestible Electronic Materialsmentioning
confidence: 99%